Promoting Psychological Well-Being Through an Evidence-Based Mindfulness Training Program - Tang, Yi-Yuan; Tang, Rongxiang; Gross, James J. (Frontiers in Human Neuroscience, 2019)
Psychological well-being is a core feature of mental health, and may be defined as including hedonic (enjoyment, pleasure) and eudaimonic (meaning, fulfilment) happiness, as well as resilience (coping, emotion regulation, healthy problem solving). To promote psychological well-being, it is helpful to understand the underlying mechanisms associated with this construct and then develop targeted and effective training programs. In this perspective paper, we discuss key components and potential brain-body mechanisms related to psychological well-being and propose mindfulness training as a promising way to improve it. Based on a series of RCT studies of one form of mindfulness training in adolescents and adults, the integrative body-mind training (IBMT), we use IBMT as an exemplar to provide research evidence of the positive effects of mindfulness training on psychological well-being. We focus on one of the mechanisms by which IBMT enhances psychological well-being – the interaction between mind (mindfulness) and body (bodifulness) -- which involves both the central nervous system and the autonomic nervous system. We also highlight the role of brain self-control networks, including the anterior cingulate cortex/prefrontal cortex (ACC/PFC), in improving psychological well-being. We suggest that mindfulness training may be a promising program that promotes the synergistic engagement of mind and body to achieve the goals of enhancing psychological well-being.